Hereditary Sensory and Autonomic Neuropathy Type IV in 9 Year Old Boy: A Case Report - AZADVARI, Mohaddeseh (Iran J Child Neurol, 2016)
Objective The Hereditary Sensory and Autonomic neuropathy (HSAN) is a rare group of neuropathies that affects the Sensory and Autonomic nervous system. The patients do not have the ability of sensing different sensations such as pain and temperature, which tends to lead to different injuries. In addition, due to autonomic involvement, the patients suffer from fluctuation in body temperature periodically and lack of precipitation. HSAN is divided into 5 types according to the age of onset, clinical features, and inheritance. Our case was a 9-yr old boy from cousin parents. He had some developmental delay and history of recurrent fever and convulsion in the first year of his life. Gradually, other symptoms added to patient’ feature such as multiple painless skin ulcers, tooth loss, destruction of toes and fingers. In electrodiagnostic study, we found decreased amplitude of sensory nerves, while the other studies were normal. Laboratory test and imaging studies were also normal. All clinical and paraclinical findings were in favor of HSAN type IV. There is no cure for such patients; as a result, these patients and their families need receiving appropriate education and timely rehabilitation services.